2023
DOI: 10.3389/fonc.2023.1105100
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical radiomics-based machine learning versus three-dimension convolutional neural network analysis for differentiation of thymic epithelial tumors from other prevascular mediastinal tumors on chest computed tomography scan

Abstract: PurposeTo compare the diagnostic performance of radiomic analysis with machine learning (ML) model with a convolutional neural network (CNN) in differentiating thymic epithelial tumors (TETs) from other prevascular mediastinal tumors (PMTs).MethodsA retrospective study was performed in patients with PMTs and undergoing surgical resection or biopsy in National Cheng Kung University Hospital, Tainan, Taiwan, E-Da Hospital, Kaohsiung, Taiwan, and Kaohsiung Veterans General Hospital, Kaohsiung, Taiwan between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Generally speaking, deep learning models outperformed the ML models; however, deep learning models are more complex and require more parameters, huge amounts of data, and high computational cost. In our recent study, we found that the radiomics-based ML model had superior performance compared to the 3D conventional neural network (CNN) model within a limited dataset [29]. Due to the limited sample size, the present study focused on the development of ML models using both clinical features and radiomics.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Generally speaking, deep learning models outperformed the ML models; however, deep learning models are more complex and require more parameters, huge amounts of data, and high computational cost. In our recent study, we found that the radiomics-based ML model had superior performance compared to the 3D conventional neural network (CNN) model within a limited dataset [29]. Due to the limited sample size, the present study focused on the development of ML models using both clinical features and radiomics.…”
Section: Discussionmentioning
confidence: 98%
“…Compared with other clinical-radiomics model studies that limited specific PMT histology types [27][28][29], this study did not set restrictions on PMT subtypes, including 12 different PMT subtypes. In addition, unlike other clinical-radiomics model studies aimed to improve differential diagnosis [27][28][29], the developed voting ensemble ML model may be utilized as a clinical decision support system to help the selection of initial management for patients with PMTs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, researchers have successfully achieved good discriminative performance in distinguishing low-grade and high-grade meningiomas using the LightGBM algorithm for both radiomics and deep learning models(Yang et al 2022). Similarly, Chang et al constructed LightGBM and convolutional neural network (CNN) models based on non-contrast CT and enhanced images to differentiate thymic epithelial tumors from other anterior mediastinal tumors(Chang et al 2023). The results demonstrated that the LightGBM model outperformed the CNN model in both the non-contrast CT dataset and the enhanced CT dataset.…”
mentioning
confidence: 99%